Gender Analysis of Crop and Animal Husbandry Practices in Hill Agriculture - Singh, Ashish; Kumbhare, N. V.; Singh, Premlata; Sharma, Nishi; Patel, Neelam; Gurung, Bishal (Indian Journal of Extension Education, 2016)
Women farmers have been the vital workforce in agriculture, as they manage agricultural activities along with the  household chores. The study was conducted in purposively selected Almora and Nainital districts of Uttarakhand, India.  The two blocks each from Almora (Takula and Hawalbagh) and Nainital (Betalghat and Dhari) were selected randomly.  Further, two villages from each block were selected randomly. Fifteen women and five men farmers from each village  were selected through simple random sampling. Thus, a total of 120 women and 40 men respondents from two districts  constituted the sample for the study. The study revealed gender gap in crop husbandry, animal husbandry and daily routine  practices in hill agriculture. The gender analysis in crop husbandry practices revealed that a majority of the women  farmers were engaged in weeding (94.60%) followed by thinning and gap filling (87.82%), storage (82.23%), threshing  and winnowing (74.77%), irrigation (70.52%), loading and unloading (63.58%) were the major activities done by women  farmers. Agricultural activities like sowing (66.46 %), seed treatment (51.42%) and harvesting (52.33%) were done by  women farmers with a significant help from men farmers. The activities like fodder cutting (88.27%) and cleaning animal  shed (86.75%) were the activities demand larger time share of women farmers. Other activities like feed and fodder to the  animals (70.47%), milking (75.67%) and animal care (77.50%) were also majorly done by women. Most of the activities  like food preparation (99.00%) followed by collection of fuel and fodder (97.00%), collecting water (89.40%) and family  care (88.20%) were the major time consuming activities done by the women farmers as compared to their male  counterpart.
Keywords: Gender analysis; hill agriculture; animal husbandry